Sorptive removal of selected emerging contaminants using biochar in aqueous solution - Kim, Eunseon; Jung, Chanil; Han, Jonghun; Her, Namguk; Park, Chang Min; Jang, Min; Son, Ahjeong; Yoon, Yeomin (Journal of industrial and engineering chemistry (Seoul, Korea), 2016)
The adsorption of sunscreen compounds (benzophene [BZP] and benzotriazole [BZT]) and widely known endocrine-disrupting compounds (bisphenol A [BPA] and 17 β-estradiol [E2]) was investigated using commercially available powdered activated carbon (PAC) and activated biochar produced in the laboratory. The removal efficiency by biochar was approximately 5–30% higher than that by PAC depending on experimental conditions, presumably due to the higher surface area and pore volume of biochar. The removal of compounds followed the order E2>BZP>BPA>BZT:Kf (μg/g)/(mg/L)1/n, Freundlich affinity coefficients, were as follows – 19.7, 19.7, 6.57, and 4.56 for PAC, and 30.2, 28.4, 9.22, and 6.79 for biochar. An increase in pH from 3.5 to 10.5 decreased the adsorption of BZP, BZT, BPZ, and E2 by 11.5, 11.4, 10.7, and 4.7% by biochar, respectively. Overall, biochar had a higher adsorption capacity for all chemicals tested compared with PAC.